Peranan Kepala Madrasah Aliyah dalam Meningkatkan Kinerja Guru pada Ma’had Darud Da’wah Wal-Irsyad di Pangkajene Sidrap - M Tahir (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract The purpose of this research was to determine the role of Madrasah Chief in developing teacher’s performance, so that the recearch’s centre point was the existence of trust and responsibility held by Madrasah Chief, along with all influencing factors to all teachers’ performance at Madrasah Aliyah of Ma'had Darud Da'wah Wal-Irsyad in Pangkajene, Sidrap Regency. The research used quantitative method, started with collecting data archives and documentaries and followed with an interview. Data collection from the research were then percentaged cumulatively. Then reseacher used questionnaire to get inferrential data from all respondents consisted of teachers. The results showed a quite good teachers’ performance at Madrasah Aliyah of Ma'had Darud Da'wah Wal-Irsyad in Pangkajene. The Madrasah Chief had also showed a good and optimal role to develop more performance. So the results from interview were expected to give a solution to all stakeholder from each departement to develop educational quality in the future. I do hope this research will be a referrence and barometer about teacher’s performance against the role of Madrasah Chief of Madrasah to develop the education level at Madrasah Aliyah of Ma'had Darud Da'wah Wal- Irsyad in Pangkajene Sidrap Regency.